1989
DOI: 10.1002/1097-0355(198921)10:1<45::aid-imhj2280100105>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up of children identified with and treated for a motor delay of nonspecifiable etiology

Abstract: Forty‐eight 7‐ to 8‐year‐old children who had been diagnosed prior to 48 months of age as being developmentally motor delayed and had received therapy for their delay were followed up and assessed for motor, intellectual, and psychological development as well as for self‐perceived competence and school achievement. These children were found to be significantly inferior on all of these variables, except for self‐competence, when compared with matched nondelayed controls. Those delayed children who had begun tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Therefore, interventions supporting motor skills early in a child's life might also be beneficial for language development. Moxley-Haegert and Ladd (1989) showed that treatment beginning before 24 months of age demonstrated greater gains in motor and cognitive function than treatment beginning after 24 months. As an example of this, teaching an infant to creep has been demonstrated to have transfer effects not only on the development of other locomotor skills but also on cognitive development (Lagerspetz et al 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, interventions supporting motor skills early in a child's life might also be beneficial for language development. Moxley-Haegert and Ladd (1989) showed that treatment beginning before 24 months of age demonstrated greater gains in motor and cognitive function than treatment beginning after 24 months. As an example of this, teaching an infant to creep has been demonstrated to have transfer effects not only on the development of other locomotor skills but also on cognitive development (Lagerspetz et al 1971).…”
Section: Discussionmentioning
confidence: 99%
“…On examination of the literature about intervention for 'children whose primary problem is one of poor co-ordination, it becomes clear that programmes designed specifically to treat this condition are few (Moxley-Haegert and Ladd 1989). In 4 clinical practice, programmes originally d designed for other groups are used to treat 2clumsiness, such as perceptual-motor training (Kephart 1960), the Frostig programme (Frostig 1968), and sensory integrative therapy (Ayres 1972).…”
mentioning
confidence: 99%